Pelatihan Senam Asma Menuju Desa Sehat - RahmaNova Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
The problem that arises at this time is that the level of health for villagers is not yet optimal because the role of health cadres is not optimal, especially health problems that are not contagious (non-communicable disease) such as asthma. Asthma can not be cured but can be controlled either with drugs or without drugs. One of the recommended management of asthma without drugs by WHO and the Global Initiative for Asthma (GINA) is exercise or physical exercise. Asthma gymnastics is a recommended physical exercise in Indonesia and many studies have been carried out both on increasing lung capacity function and improving quality of life. The solution to the problems raised in this community service will train cadres to understand more about asthma and asthma exercise training which will be given for 3 months a week 3 times every Friday, Saturday and Sunday to health cadres so that it is hoped that there will be a special place for patients asthma to improve quality of life. Friday and Saturday are used for training health cadres on asthma exercise, and Sunday for people with asthma. The target of this community service is health cadres and people with asthma consisting of 56 people, 11 health cadres and 45 people with asthma. The results of the service obtained data, 11 cadres were able to do asthma exercise independently and people with asthma experienced an increase in their quality of life. The measuring instrument used for the quality of people with asthma is the Asthma Quality of Life Questionnaire (AQLQ)